KINERJA PENGIRIMAN BARANG EKSPOR - Sarinah Sihombing; Widya Eka Purnamasari (Institut Transportasi dan Logistik Trisakti, 2014)
The level of customer interest in the services provided by PT. Supra Raga Transport is very important that is 57.48%. In quadrant A Cartesian diagram which factors or attributes are considered to affect customer satisfaction, but the company has yet to carry out the wishes of customers, a factor that is included in this quadrant is the precision and accuracy of the delivery time and the exports and the ability of employees to be responsive in handling the export documents. The level of conformity, to service an average of the results of the variable x is 4.17%, the average results for the variable y is 4.38% and there are two elements of the 10 elements that must be corrected. The results for the level of concordance between the level of performance of the service to the importance of services in the amount of 99.48% which shows very satisfied